Comparative Effects Of Stabilizing Exercises and PNF Stretching Of Upper Trapezius On Functional Disability & Pain - Iqra Ashraf, Sidra Manzoor, Abdullah Khalid Khan, Yasha Sajjad, Navera Fatima, Romaisa Javed (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the results of proprioceptive neuromuscular facilitation stretches with stability exercises of upper trapezius in reference to neck ranges, disability level and pain specifically in mobile phone users with neck pain. Methods: Convenient sampling was used with randomization at the time of group allocation and blinding of assessor was made sure. 50 subjects both males and females with neck pain were recruited with 18 to 30 years of age. 2 treatment groups were present each containing equal number of subjects. One group was treated using stretches and other was given stability exercises. Neck disability index was used to record level of disability for neck and Numeric pain rating scale was used for recording pain levels at baseline, 4th and 8th weeks after treatment. Study was completed in 9 months. Results: Both groups showed no important difference with p > 0.05. However, both groups indicated significant changes in pain intensity and neck functionality at 4th and 8th weeks when compared with baseline. Conclusion: Both techniques were equally effective in improving neck ranges, pain levels and neck functionality.